Effect of mining subsidence on soil erosion in mountainous area of the Loess Plateau - Huang, Yi; Wang, Yunjia; Wang, Meng; Tian, Feng; Ao, Jianfeng (Nong ye gong cheng xue bao, 2014)
In this paper, based on mining subsidence rules and models, a DEM of the subsidence area was constructed referring to the subsidence parameters in the research area. On this basis, the soil erosion changes of three major factors-slope, slope length factor, and vegetation coverage factor caused by mining subsidence in a revised universal soil loss equation in mountainous area were measured for the first time, and the other three parameters that were not disturbed by mining in a revised universal soil loss equation were calculated according to relevant research studies. The results showed that: From 2001-2010, the average slope decreased by 0.025[degrees], caused by mining in the study area, average slope length factor decreased by 0.139, the area that soil erosion unchanged,reduced and increased in subsidence area was respectively3.083,3.412 and 4.707km super(2), and the area in which soil erosion reduced and increased out of the subsidence area was respectively 0.143 and 0.023km super(2).